2001
DOI: 10.1093/heapro/16.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific health behaviors of German university students predict the interest in campus health promotion

Abstract: This cross-sectional study aimed to provide an assessment of the needs for health promotion in university freshmen, based on lifestyle variables and the interest in health-promoting activities. A questionnaire survey was performed using a sample of 288 male and 362 female university freshmen from 19 to 33 years of age. Male students were significantly more likely to engage in drug-taking behaviors, referring to alcohol and cannabis use, and had a higher body mass index. No gender difference was noted in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
77
3
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 23 publications
17
77
3
12
Order By: Relevance
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 59%
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, previous FFQ validation studies have found significant differences between sexes (38) , unlike the present study, which found no significant difference between the number of males and females recruited. Nevertheless, FFQ validation studies typically have greater numbers of female than male participants (25,39) , which could be a result of females being more likely to take part in scientific studies (40) , particularly nutrition studies, possibly because of an increased interest in the subject area (41) .…”
Section: Discussionmentioning
confidence: 99%
“…Just like in another study which showed females tend to keep a more balanced diet. 9 The last hypothesis claimed that a positive relationship would be observed between eating habits and BMI. Surprisingly, in this study, the relationship was not significant.…”
Section: Discussionmentioning
confidence: 99%